2018
DOI: 10.1111/jdi.12892
|View full text |Cite
|
Sign up to set email alerts
|

Brown rice‐specific γ‐oryzanol as a promising prophylactic avenue to protect against diabetes mellitus and obesity in humans

Abstract: Chronic overconsumption of animal fats causes a variety of health problems, including diabetes mellitus and obesity. Underlying molecular mechanisms encompass leptin resistance, a decrease in rewarding effects of physical activities, xanthine oxidase-induced oxidative stress in vasculature and peripheral tissue, impaired activation of incretin signaling, deviation in food preference, and dysbiosis of gut microbiota. Based on our clinical observation that daily intake of brown rice effectively ameliorates bodyw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 29 publications
0
29
0
2
Order By: Relevance
“…Mice and cellular experiments have revealed that BR specific γ‐oryzanol acts as a molecular chaperone, ameliorates reticulum stress in hypothalamus, protects β‐cells against apoptosis, and inhibits DNA methyltransferases in brain reward system. Therefore, partly attenuating the high‐fat‐diet preference via the epigenetic modulation of striatal dopamine D2 receptor, improves fuel dyshomeostasis, and improves insulin resistance (Kozuka et al., , ; Masuzaki et al., ). The germination was also found to enhance antidiabetic potential of BR.…”
Section: Potential Health Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice and cellular experiments have revealed that BR specific γ‐oryzanol acts as a molecular chaperone, ameliorates reticulum stress in hypothalamus, protects β‐cells against apoptosis, and inhibits DNA methyltransferases in brain reward system. Therefore, partly attenuating the high‐fat‐diet preference via the epigenetic modulation of striatal dopamine D2 receptor, improves fuel dyshomeostasis, and improves insulin resistance (Kozuka et al., , ; Masuzaki et al., ). The germination was also found to enhance antidiabetic potential of BR.…”
Section: Potential Health Benefitsmentioning
confidence: 99%
“…The concentration of these nutrients and bioactive compounds may vary depending on influences such as rice variety, production environment or geographical origin, and postharvest treatments or processing conditions. The whole BR grain, germinated BR grain (GBR), or their derived extracts and fractions have shown several potential health benefits such as antioxidant, antidiabetic, anticancer, neuroprotective, and cholesterol lowering effects (Chompoopong et al., ; Chung, Rico, Lee, & Kang, ; Li, Chou, & Shih, ; Lim, Yong, Mohtarrudin, & Loh, ; Masuzaki et al., ; Pang et al., ). Therefore, the objective of this work is to review the last updates in research performed for purposes of evaluating of nutritional quality and potential health benefits of the whole BR to provide recent information to interested researchers and consumers, which may help in promotion of the whole BR consumption as a promising functional food and for its potential contribution to human well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…diabetes [3], and obesity [4][5][6][7], and some interventional studies for Type 2 diabetes [9][10][11]. It has been reported that brown ricederived γ-oryzanol can act on the brain reward system [18]. The system is related to satisfaction of the meals, and it is attenuated in obese humans.…”
Section: Discussionmentioning
confidence: 99%
“…This fraction in rice bran oil and extracts is associated with cholesterol lowering properties (Cicero & Gaddi, 2001). Furthermore, in animal models, γ-oryzanol was shown to reduce preference in obese mice for choosing high animal fat food, thus having the potential to decrease the risk of obesity (Masuzaki et al, 2019). It was also shown to protect β-cells of the pancreatic islets against apoptosis, therefore having protection against developing diabetes mellitus (Masuzaki et al, 2019).…”
mentioning
confidence: 99%